2021
DOI: 10.1590/0366-69132021673823099
|View full text |Cite
|
Sign up to set email alerts
|

Sintering mechanisms of partially stabilized zirconia (TZ3Y) with ZnO and Co3O4 as sintering additives

Abstract: In this work, the sintering mechanisms of 3 mol% yttria-stabilized zirconia (TZ3Y) and TZ3Y containing 0.3 wt% of ZnO or Co 3 O 4 were analyzed by determining the apparent activation energy of sintering from dilatometry data and observing the evolution of microstructure. Dilatometry test was performed at a heating rate ranging from 5 to 20 °C/min from room temperature up to 1500 °C. The main mechanism of each sintering additive for the studied samples was revealed from the variation of the sintering activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…It was found that activation energies of nominally pure alumina and zirconia were 670 and 580 kJ/mol in longitudinal orientation and 700 and 550 kJ/mol in transversal orientation, respectively. These values fit the previously reported data in the literature covering a big scatter in the range of 342 -1163 kJ/mol for alumina [1-4, 7-13, 21, 22, 51] and 310 -990 kJ/mol for zirconia [3,9,[14][15][16]22]. The broad values spread is given by evaluation method, morphology [7] and purity of the powder used, considered density interval [14,52,53], different microstructure before sintering and temperature range [9].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It was found that activation energies of nominally pure alumina and zirconia were 670 and 580 kJ/mol in longitudinal orientation and 700 and 550 kJ/mol in transversal orientation, respectively. These values fit the previously reported data in the literature covering a big scatter in the range of 342 -1163 kJ/mol for alumina [1-4, 7-13, 21, 22, 51] and 310 -990 kJ/mol for zirconia [3,9,[14][15][16]22]. The broad values spread is given by evaluation method, morphology [7] and purity of the powder used, considered density interval [14,52,53], different microstructure before sintering and temperature range [9].…”
Section: Resultssupporting
confidence: 88%
“…A lot of works have been published up to now to establish activation energies of nominally monolithic ceramics. The most attention was paid to alumina [1][2][3][7][8][9][10][11][12][13], zirconia [3,7,9,[14][15][16], silicon nitride [17], zinc oxide [8], uranium dioxide [18,19], yttrium oxide [20], etc. Moreover, it was found that the sintering technique can also play a role in diffusion mechanisms in studied materials affecting the activation energy of sintering [8].…”
Section: Su and Johnsonmentioning
confidence: 99%